Use of mobile app “SUPPORT+” to enhance community palliative care in patients with advanced cancer: A prospective study - Wing-Lok Chan; Yin-Ling Tai; Wai-Kwan Steven Siu; Holly Li-Yu Hou; Kwok-Keung Yuen; Victor Ho-Fun Lee (Palliative Care and Social Practice)
Background: Patients with advanced cancer often experience symptoms between clinic visits, leading to emergency department admissions. Integrating patient-reported outcome measures into care could enhance symptom monitoring and support. Aim: This study assesses the feasibility and efficacy of the SUPPORT+ app for monitoring symptoms and providing timely interventions for patients with advanced cancer. Design: In this prospective feasibility study, patients used the SUPPORT+ app for weekly symptom monitoring over 16 weeks. Participants received self-management advice from the app and timely remote consultations from palliative care nurses. Assessments included questionnaires on psychological stress, app satisfaction, and palliative care knowledge, with medical records reviewed for emergency department visits and unplanned hospitalizations. Setting and participants: Patients with advanced cancer receiving community palliative care and owning smartphones were recruited from an outpatient palliative care clinic at a university hospital in Hong Kong. Results: A total of 109 patients were recruited, with 84 completing the study (retention rate: 78.4%). Over 90% reported their symptoms weekly. Significant increases were noted in advance directive completion (9.5% vs 22.6%, p  = 0.047) and discussions on preferred places of dying (14.3% vs 28.6%, p  = 0.044), alongside a decrease in depression scores (8.4–6.7, p  = 0.024). Most participants found the app easy to use and reported positive health effects. Conclusion: The SUPPORT+ app demonstrated feasibility and acceptability in facilitating end-of-life communication, increasing advance directive completion, and potentially reducing depression in patients with advanced cancer. Further research, including randomized controlled trials, is needed to establish its efficacy.